Auditing Organizations Through a Strategic-System Lens (Book). - Williams, Thomas H.; Rittenberg, I. Arry E. (The Accounting Review, 1998)
Abstract Reviews the book "Auditing Organizations Through a Strategic-System Lens," by Timothy Bell, Frank Marrs, Ira Solomon and Howard Thomas.